Recent perspectives in dynamic testing and monitoring of bridges - cunha, a (2013)
The paper reviews some of the most recent aspects involved in the dynamic testing and continuous monitoring of bridges. This includes a discussion of testing techniques, instrumentation, modal identification and damage detection. On the basis of their experience, the authors described several case studies in which some of the most recent developments have been used to accomplish different purposes: the Millau Viaduct, in France, the Pedro e Ines footbridge and the Infante D. Henrique Bridge, in Portugal, and the Grande Ravine Viaduct, at the Reunion Island. Copyright (c) 2012 John Wiley & Sons, Ltd.